A Study of Unmanned Store Adoption among University Students: A Control Variable Perspective - Eszter Szabó-Szentgróti; Petra Kinga Kézai; Szabolcs Rámháp (Decision Making: Applications in Management and Engineering, 2025)
In the past nine years, a significant trend has emerged in the retail sector with the rise of cashier less and unmanned stores. This technological innovation is becoming increasingly widespread across various countries, although its availability remains somewhat limited in Hungary. The current study investigates the extent to which students in Hungarian higher education institutions are willing to adopt this technology. It explores the factors influencing attitudes toward cashierless shopping, using the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) as the theoretical framework. Seven hypotheses were formulated based on a comprehensive review of existing literature and research models. In addition to these core hypotheses, the study also assessed whether three control variables income, gender, and location had an impact on key latent variables within the model. Data collection was conducted via an online questionnaire, which garnered responses from 843 participants. The study employed variance-based structural equation modelling (PLS-SEM) to analyse and test the proposed research model. The results revealed that performance expectancy, effort expectancy, social influence, and hedonic motivation had a strong and positive influence on behavioural intention toward using cashier less stores. Regarding the control variables, significant relationships were identified between income and atmosphere variable, as well as income and price sensitivity. Furthermore, gender was found to have a significant influence on hedonic motivation, suggesting that these demographic factors play a moderating role in shaping attitudes toward unmanned store technology. The findings of this study provide valuable insights for practitioners and policymakers in the retail industry who are considering the implementation of cashier less technology. The diffusion of this technology is expected to grow, making it crucial to investigate factors that influence not only intentions but also the actual use of unmanned stores.